The Development of an Enhanced Smart Saltwater Desalination System - Badrulhisam, Muhammad Afiq; bt Rosdi, Nurnaylie Aisha; Mokhter, Faezahana; Soon, Chin Fhong (Emerging Advances in Integrated Technology, 2023)
Water is an essential resource for life. We also know that water scarcity is a huge problem that happens around the world and especially in countries that have low economies and large populations. This thesis proposes desalination system based on solar panels for enhancing the desalination process. This project aims to produce clean water from the salt water using the concept of evaporation and the result that comes from this project is to produce a desalination system that can treat salt water to clean water not just during the day but also at night. In this project, the desalination system works by solar heating which sunlight will heat the salt water in the basin to produced evaporated water and the bulb will replace sunlight during night since its capability works same as sunlight.